Generalizable Middleware to Support Use of REDCap Dynamic Data Pull for Integrating Clinical and Research Data - Campion, Thomas R. (AMIA Jt Summits Transl Sci Proc, 2017)
To support integration of clinical and research data, the makers of REDCap, a widely-used electronic data capture system, released the Dynamic Data Pull (DDP) module. Although DDP is a standard module in REDCap, institutions must develop custom middleware web services to exchange data between REDCap and local source systems. The lack of middleware is a barrier to institutional adoption and use by investigators. To overcome this gap, we developed a REDCap DDP web service middleware (accessible at https://github.com/wcmc-research-informatics/redcap-ddp) that minimizes developer effort, relies on configuration by non-developers, and can generalize to other settings. Early findings suggest the approach is successful.